Experiment study on performance of abrasive slurry jet with or without high polymer in stainless steel machining. Issue 5 (March 2018) - Wang, Fengchao; Xu, Qiwen; Feng, Dachuan; Guo, Chuwen
Abstract Abrasive slurry jet (ASJ) with high polymer converges better than the one without it does, which has significant advantages in the cutting capability and quality in material processing. The paper carried out two groups of experiments to study the performance of ASJ with or without polymer additives in stainless steel cutting. In the first one, full factorial design method was used to study the effects of parameters (pressure, high-polymer mass concentration, and traverse speed) on cutting depth and kerf width. And a dimensionless model for predicting cutting depth was established with multivariable linear regression calculation. The orthogonal experimental method was adopted in the second group of experiments to study the effects of parameters (pressure, high-polymer mass concentration, traverse speed, and stand-off distance) on surface roughness with the range analysis and variance analysis method. And the surface roughness partition in ASJ cutting was obtained. The conclusions of the paper can provide technical guidance in material processing with ASJ.